The Influence Of Liquidity And Profitability On Firm Value Through Educational And Organizational Management Approaches In Manufacturing Companies Listed On The Indonesia Stock Exchange - Yusri Yunus; M. Ikhwan Maulana Haeruddin; Anwar; Nurman; Annisa Paramaswary Aslam (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2026)
This study aims to analyze the influence of liquidity and profitability on firm value through the perspectives of educational and organizational management in manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employed a quantitative approach using a causal research design and explanatory method. The population consisted of 109 manufacturing companies in the basic and chemical industry subsector, while the sample comprised 19 companies selected through purposive sampling, resulting in 95 panel data observations. Secondary data were obtained from annual financial statements published on the Indonesia Stock Exchange website and corporate websites. Liquidity was measured using the Current Ratio (CR), profitability using Return on Assets (ROA), and firm value using Price to Book Value (PBV). Data analysis was conducted using panel data regression analysis with EViews 13 software. The results indicate that liquidity has a negative and significant effect on firm value, while profitability has a positive and significant effect on firm value. The findings also reveal that organizational effectiveness, leadership quality, institutional learning, and strategic resource management contribute to improving corporate competitiveness and sustainability. From the perspective of educational and organizational management, financial performance reflects managerial effectiveness and institutional governance quality in strengthening public trust and firm value in the capital market.